A Case of Lenition-Fortition and Honorific Asymmetry in Limbu Native's Nepali Speech - Tumbahang, Mohan Kumar (Dristikon: A Multidisciplinary Journal, 2022)
This article aims to observe why deviations occur in the Limbu natives' speech while speaking the Nepali language. The objective of the study is to find out the factors which are responsible for the distorted form of Nepali speech uttered by the Limbu natives. Basically, the analysis is based on the phonological and sociolinguistic theories. The phonological aspect is concerned with the sound system of both languages. From the sociolinguistic aspect, Nepali and Limbu languages have a sharp contrast in the use of honorific expressions. In the process of analysis, the study has revealed that the Limbu language has less number of sounds than the Nepali language. In addition, eight consonants play a crucial role to cause the deviation in Nepali speech uttered by the Limbu natives. The Nepali language exhibits the five-layered honorific pronominal subjects with parallel verb conjugations. In contrast, the Limbu does possess only one form. The article can be useful to create a way for interested individuals to deepen their understanding of the reasons behind the deviations committed by the native of one language-speaking another language.